A Serological Assay for the Detection of Antibodies Generated Against California Serogroup Virus Infection - Stulberg, Alyssa; Barry, Christina; Robinson, Alyssia; Mueller, Nicole; Bello, Alexander; Wood, Heidi (Methods in molecular biology (Clifton, N.J.), 2025)
The California serogroup (CSG) viruses are orthobunyaviruses endemic in North America and responsible for the second most common cause of mosquito-borne viral encephalitis in the United States. As the CSG viruses have been neglected and are poorly studied, there are no commercial diagnostic serological assays or reagents available for detection. Therefore, diagnostic laboratories have had to rely on the development of their own in-house serological assays. To develop serological assays, antigenic materials such as recombinant protein, virus-like particles (VLP), or inactivated virus can be used in the IgM antibody capture enzyme-linked immunosorbent assay (MAC-ELISA) to detect CSG virus-specific IgM antibodies. All positive MAC-ELISA results should be confirmed by a well-defined gold standard test method such as the plaque-reduction neutralization test (PRNT).